PERBANDINGAN KADAR KURKUMIN DARI EKSTRAK KUNYIT DAN TEMULAWAK YANG DITENTUKAN DENGAN METODE SPEKTROFOTOMETRI VISIBLE - Safrida Safrida; Anny Sartika Daulay (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Turmeric (Curcuma longa L.) is one of the plants known by the public as a spice that has many health benefits. Temulawak (Curcuma zanthorrhiza Roxb.) is one of Indonesia's rich spices that has been known for its benefits and properties since time immemorial. Curcumin is a natural chemical compound found in turmeric and ginger. The purpose of this study was to determine the levels of curcumin by using visible spectrophotometric methods from extracts of turmeric and temulawak using water as a solvent with the decoctation method. The extraction method chosen in this study is the decoctation method. Turmeric and temulawak were extracted by weight ratio of turmeric and solvent 1:3 at a temperature of 90ºC for 30 minutes. The results of this decoctation are separated by decantation. In the results of this liquid extract of turmeric and temulawak, a qualitative test of curcumin was determined using the thin layer chromatography (TLC) method with silica gel 60 F254 as stationary phase and chloroform: ethanol: glacial acetic acid (94: 5: 1) as mobile phase. Then the determination of curcumin levels in turmeric and temulawak extracts was carried out quantitatively using the visible spectrophotometric method. The results of the qualitative test using thin layer chromatography (TLC) obtained the value of curcumin Rf 0.54, turmeric extract Rf 0.54, temulawak extract Rf 0.54. The maximum wavelength obtained is 425.14 nm with an absorbance of 0.428. In determining the calibration curve, the regression equation y = 0.14114x-0.00452 is obtained with r = 0.99963. The levels of curcumin obtained using visible spectrophotometric methods are turmeric extract 80,91088± 1,83864 mg/gand temulawak extract 48,81070± 0,75803 mg/g.